Development and Contribution of the Agricultural Sector to Gross Regional Domestic Products (GDP) Waropen District - Waspada Meliala (Budapest International Research and Critics University, 2022)
The development of the agricultural sector in Waropen Regency has a trend line slope of 295,562 with a positive direction meaning that the trend of the agricultural sector in the RegencyWaropen during the period 2009 - 2015 had an increasing trend from year to year with an average increase of 18,310.9 or Rp. 18,310,900,000,- . Quantitative Research Methods. The results showed that the average contribution of the agricultural sector to the Gross Regional Domestic Product (Economic Development) in Waropen Regency during the 2009 - 2015 period was 35.54% per year. The development of the agricultural sector in Waropen Regency from 2009 to 2015 shows a situation that tends to increase from year to year. However, if you look at its contribution to Gross Regional Domestic Product (GRDP) or Economic Development, the contribution of the agricultural sector from year to year tends to decrease. The contribution of the agricultural sector from year to year tends to decrease due to several factors, including; The amount of the contribution of each sub-sector, the role of society, government policies, and the availability of natural resources.